Concurrent sexual partnerships and racial disparities in HIV infection among men who have sex with men. Issue 5 (22nd September 2009) - Bohl, D D; Raymond, H F; Arnold, M; McFarland, W
Abstract : Objectives: To measure the level of sexual partner concurrency and assess its potential role in explaining disparities in HIV prevalence by race/ethnicity among men who have sex with men (MSM). Methods: A cross-sectional, community-based survey of MSM in San Francisco was conducted in 2008 using time-location sampling. Four different measures of sexual partner concurrency were assessed and compared across race/ethnicity groups: overlap in time with the most recent sexual partners, knowledge of the most recent sexual partner having other partners, any overlap with up to the last five partners and complete overlap with up to the last five partners. Results: A total of 521 MSM was recruited; 10% self-described their race/ethnicity as black, 62% as white, 25% as Latino and 9% as Asian (not mutually exclusive). Black MSM had fewer sexual partners overall, yet had three times the odds that all their partnerships were concurrent compared with non-black MSM (39% vs 17%, respectively, p = 0.034). None of the other measures of concurrency showed racial/ethnic differences. MSM whose partnerships were completely concurrent had a higher number of sexual episodes and unprotected sexual episodes per partnership compared with those whose partners were not completely concurrent. Conclusions: Findings support the hypothesis that the sexual networks of black MSM rather than individual behaviours account for their higher prevalence of HIV compared with non-black MSM. There remains the need specifically to validate different concurrency measures in larger samples and directly assess them as risk factors for acquiring HIV infection.